Cardiovascular magnetic resonance determinants of ventricular arrhythmic events after myocardial infarction. Issue 6 (29th November 2021) - Jáuregui, Beatriz; Soto-Iglesias, David; Penela, Diego; Acosta, Juan; Fernández-Armenta, Juan; Linhart, Markus; Ordóñez, Augusto; San Antonio, Rodolfo; Terés, Cheryl; Chauca, Alfredo; Carreño, José M; Scherer, Claudia; et al.
Abstract: Aims: To non-invasively characterize, by means of late gadolinium enhancement cardiac magnetic resonance (LGE-CMR), scar differences, and potential variables associated with ventricular tachycardia (VT) occurrence in chronic post-myocardial infarction (MI) patients. Methods and results: A case–control study was designed through retrospective LGE-CMR data analysis of chronic post-MI patients (i) consecutively referred for VT substrate ablation after a first VT episode ( n  = 66) and (ii) from a control group ( n  = 84) with no arrhythmia evidence. The myocardium was characterized differentiating core, border zone (BZ), and BZ channels (BZCs) using the ADAS 3D post-processing imaging platform. Clinical and scar characteristics, including a novel parameter, the BZC mass, were compared between both groups. One hundred and fifty post-MI patients were included. Four multivariable Cox proportional hazards regression models were created for total scar mass, BZ mass, core mass, and BZC mass, adjusting them by age, sex, and left ventricular ejection fraction (LVEF). A cut-off of 5.15 g of BZC mass identified the cases with 92.4% sensitivity and 86.9% specificity [area under the ROC curve (AUC) 0.93 (0.89–0.97); P  < 0.001], with a significant increase in the AUC compared to other scar parameters ( P  < 0.001 for all pairwise comparisons). Adding BZC mass to LVEF allowed to reclassify 33.3% of the cases and 39.3% of the controls [net reclassification improvement = 0.73 (0.71–0.74)]. Conclusions: The mass of BZC is the strongest independent variable associated with the occurrence of sustained monomorphic ventricular tachycardia in post-MI patients after adjustment for age, sex, and LVEF. Border zone channel mass measurement could permit a more accurate VT risk stratification than LVEF in chronic post-MI patients. Graphical Abstract: